Corrosion Behaviour of Al/(TiB2 + -Al3Ti)-Based Functional Grade Metal Matrix Composite by Sedimentation Method - Kocaman, Engin; Aydin, Hasan; Yigit, Kenan; Caliskan, Fatih; Savas, Omer (SPRINGER INDIA, 2024)
The current study examined the producibility and corrosion behaviour of functionally graded Al-m/Al3Ti and TiB2 composites by sedimentation method. For this aim, the Al-Ti-B master alloy melted at 800 degree celsius in the crucible and kept for 90 min to ensure the sedimentation of Al3Ti and TiB2 particles. In the samples taken from different sections of the crucible via a top-down approach, it was observed that the sedimentation method is rather suitable for obtaining of FGM composite. In the Rietveld analyses conducted across the sections for the refinement of crystal structures, it was determined that the amount of particles increased from top to bottom. Corrosion tests performed in different NaCl concentrations showed that the particle fraction did not have a direct effect on the corrosion resistance of the layers. Also, the highest corrosion resistance was obtained in the D layer without particle reinforcement, corrosion resistance decreased with particle reinforcement. [GRAPHICS]
Keywords: Aluminium composites; Functionally graded materials; Corrosion; Sedimentation; Intermetallic; MATRIX COMPOSITES; AL; ALLOYS; AL2O3; AL3TI; WEAR; Metallurgy & Metallurgical Engineering